Statistical analysis and refinement of earthen embankment erosion models - Atkinson, Anthony (Kansas State University, 2024)
This study evaluates the current state of internal erosion modeling for earthwork embankments and proposes methods of expanding upon those models using modern advancements. It is part of an international initiative on the evaluation of dam safety simulation software for internal erosion performance and best practices. The primary experiments involve simulating uncertainty in the failure events of two dams with two different models, DLBreach and WinDAM C. DLBreach is a physically-based Dam/Levee Breach model developed by Wu. WinDAM C is also a physically-based dam breach model capable of analyzing both dam overtopping and internal erosion. The dams selected for the analysis include a 1.3-meter-high dam tested in the lab and a larger 15.56 meters high dam which suffered a failure in the field. The findings from these experiments are extended with further analysis on variance, sensitivity, and optimization. Finally, a regression model is trained using the results of these simulators as an inquiry into how well such a system can be captured using machine learning techniques. The results of these experiments, together with the results of the other members of the initiative, improve our understanding of the influences that users bring to using these tools. Finally, two approaches to extending these models are described, and some basic prototypes demonstrated. This extension seeks to replicate the detailed geometry of the real system which many modern models simplify away. The ongoing goal of doing this is to explore the effects these details might have on the development of the hydrograph and breach.
Keywords: Earthen embankment; Internal erosion; Computational fluid dynamics